The protective effect of miR-377 inhibitor against renal ischemia-reperfusion injury through inhibition of inflammation and oxidative stress via a VEGF-dependent mechanism in mice. (February 2019) - Liu, Zhaohui; Yang, Qiang; Wei, Qianjie; Chang, Yulin; Qu, Min; Yu, Lili
Highlights: NF-κB and MAPK signaling are activated by renal I/R. VEGF depletion by siRNA completely abrogates the impact of miR-377 on renal I/R-induced oxidative stress. I/R stimulates miR-377 expression. Abstract: MicroRNAs (miRNAs) play important roles in kidney development and maintenance of kidney physiological functions. MiR-377 has been reported to regulate inflammation in cardiac and cerebral ischemia. However, it remains unclear whether it has a similar function in renal ischemia/reperfusion (I/R). Using I/R model mice, miR-377 expression was determined by qRT-PCR in the renal tissues. Renal function was assessed by detection of the concentrations of blood urea nitrogen (BUN) and serum creatinine (Cr). Oxidative stress was evaluated by ELISA analysis of oxidation-related enzymes and molecules. Inflammatory factor concentration and other protein levels were analyzed by the ELISA assay and Western blot, respectively. Our study found that renal I/R stimulated miR-377 expression, while the inhibition of miR-377 attenuated renal I/R injury, and blocked renal I/R-induced oxidative stress and inflammation. Meantime, NF-κB and MAPK signaling were activated by renal I/R, which could also be reversed by miR-377 inhibitor. Furthermore, vascular endothelial growth factor (VEGF) depletion by siRNA completely abrogated the impact of miR-377 on renal I/R-induced oxidative stress, inflammation and renal dysfunction. In conclusion, renal I/R induced miR-377 expression, which upregulated VEGF expression to attenuate renal I/R-induced oxidative stress and inflammation, and finally ameliorated renal dysfunction.